Historia, filosofía y enseñanza de las ciencias: la aproximación actual - Matthews, M. R. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1994)
This paper traces the use of, and arguments for, the history and philosophy of science in school science courses. Specific attention is paid to the British National Curriculum proposals and .:o the recommendations of the US Project 2061 curriculum guidelines. Some objections to the inclusion of historical material in science courses are outlined and answered. Mention is made of the Piagetian thesis that individual psychoIog: cal development mirrors the development of concepts in the history of science. This introduces the topic of idealisation in science. Some significant instances are itemised where science education has, at its considerable cost, ignored work in philosophy of science. Arguments for the inclusion of the history and philosophy of science in science teacher education programmes are given. The paper finishes with a list of topical issues in present science education where collaboration between science teachers, historians, philosophers, and sociologists would be of considerable benefit.